تأثير سلفات المغنزيوم مع السّالبوتامول في علاج النَّوبة الرَّبوية الحادة - ديب غزل; الحكيم أمل; طيوب كاترين (Latakia University Journal -Medical Sciences Series, 2018)
تتراوح النّوبة الرّبوية الحادة من خفيفة إلى مُهدِّدة للحياة, ويُعدّ سلفات المغنزيوم أحد العلاجات المقترحة في تدبير النّوبة الرّبوية الحادة, وفي حين تمَّ إثبات فعاليته بالطَّريق الوريدي, لازالت المعلومات المتوفرة عن دوره بالطَّريق الإنشاقي قليلة ومتضاربة, لذا هدفت الدّراسة إلى البحث عن تأثير مشاركة سلفات المغنزيوم مع السّالبوتامول بالطّريق الإنشاقي في تدبير النّوبة الرّبوية الحادة. أُجريت دراسة تجربة سريرية عشوائية على 76 مريضاً, تمَّ توزيعهم على مجموعتين: تجريبية (40) مريضاً, ضابطة (36) مريضاً, حيث تلقت التّجريبية ارذاذ سالبوتامول مع سلفات المغنزيوم والضابطة ارذاذ سالبوتامول مع السيروم الملحي 0,9% على ثلاث جلسات بفاصل 20 دقيقة, تم َّ تقييم علامات الشِّدة التَّنفسية, الأزيز, عدد مرات التنفس, النبض, Sao2وPEF. أظهر سلفات المغنزيوم تأثير ملحوظ في تحسين عدد مرات التنفس, Sao2وPEF بدءاً من الدقيقة 20, حيث كانت P<0,05 , ولكن لم نلاحظ وجود تأثير لسلفات المغنزيوم على علامات الشّدة التنفسية, الأزيز والنبض فكانت P>0,05, كما أنّه لم نلحظ وجود آثار جانبية تُعزى إلى سلفات المغنزيوم, وبالتالي ننصح بإضافة سلفات المغنزيوم إلى السّالبوتامول بالطّريق الإنشاقي في علاج النّوبة الرّبوية الحادة. Asthma exacerbations can be frequent and range in severity from relatively mild to status asthmaticus. While the efficacy of intravenous MgSO4 hasbeen demonstrated, the informations available on its inhaled role still low and conflicting, so the study aim to investigate the effect of thecombinationof MgSO4and salbutamol in the management of acute asthma attack. A randomized clinical trial was conducted on 76 patients, divided into two groups: experimental (40) and control (36) patients. The trial received nebulised salbutamol with magnesium sulphate and control nebulised salbutamol with saline serum 0.9% on three sessions in 20 minutes. Signs of respiratory distress, wheezing, respiratory rate, pulse, Sao2 and PEF were assessed. Magnesium sulphate showed a significant effect in improving respiratory rate, Sao2 and PEF starting from the 20th minute( P <0.05), but did not observe the effect of MgSO4 in improving signs of respiratory distress, pulse and wheezing(P> 0,05), no side effects attributed to magnesium sulphate were observed.Inhaled MgSO4, incombination with salbutamol, appears to have benefits in the treatment of acute asthma attack.